IxsS7: A novel biomarker for Ixodes scapularis tick bite exposure in humans - Kelly, Patrick H.; Cummings, Derek A.T.; Iniguez, Eva; Donatelli, Tiago; Rogerio, Luana; Kotál, Jan; Martins, Larissa Almeida; Berger, Markus; Sousa-Paula, Lucas C; Lu, Stephen; Stark, James H.; Ng, Siu-Ping; et al. (Ticks and tick-borne diseases, 2025)
•IxsS7 is a novel antigenic biomarker of I. scapularis exposure in humans.•IxsS7 protein coding sequence is highly conserved in Ixodes ticks.•Sera from recombinant (r) IxsS7 immunized rabbits recognizes I. scapularis versus other genera.•rIxsS7 is recognized by IgG from humans who self-report prior tick bites. Ixodes scapularis is a primary vector of several important tick-borne pathogens including Borrelia burgdorferi sensu lato, the causative bacterial genospecies complex of Lyme disease, Babesia microti, Anaplasma phagocytophilum, Borrelia miyamotoi, Ehrlichia muris eauclarensis, and Powassan virus. Salivary compounds secreted by I. scapularis during blood feeding are immunogenic and can elicit robust antibody responses in humans which can potentially be leveraged as surrogate markers of prior tick bite exposure. In this study, we investigate the potential of a tick secreted salivary serine protease inhibitor, IxsS7, as a novel antigenic biomarker of I. scapularis exposure in humans. We demonstrate that the IxsS7 protein-coding sequence is highly conserved (>90 % identity) among other important Ixodes species (e.g., Ixodes ricinus, Ixodes persulcatus, and Ixodes pacificus) and poorly conserved (<50 % identity) with homologs from other tick genera, such as Amblyomma spp., Dermacentor spp., Rhipicephalus spp., and Haemaphysalis spp. Antibodies in sera from rabbits immunized with recombinant IxsS7 (rIxsS7) strongly recognize native IxsS7 when challenged with salivary gland homogenate (SGH) from blood-fed I. scapularis females, while showing minimal cross-reactivity with SGH from other hard tick (Ixodidae) genera. Western blot and ELISA analyses revealed that human subjects who reported recent prior exposure to ticks possessed IgG antibodies that recognized rIxsS7, highlighting its potential as a biomarker of exposure specifically against I. scapularis. Further development of serological tools that can measure human antibody responses to Ixodes-specific salivary antigens is essential to better quantify individual- and population-level risk of important tick-borne diseases such as Lyme disease.